Political empowerment of women: Case of Orissa PRIs (Note) - Panda, Snehalata (1999)
Based on time-series data on 92 women candidates elected to Gram Sabha and Panchayat Samiti levels in Orissa, the author portrays an empirical picture on performance of women representatives in Panchayati Raj system. To ascertain their performance, she covered in her survey significant contributing factors like their socio-economic and political background, factors contributing to their success in election, their political socialisation, and participation. With the help of few indicators evolved in her survey, she also indicates the direction of change in the political empowerment of women. - Reproduced
Keywords: Note; Panchayat - India - Orissa; Women - India - Orissa; Women